Empirical Evidence of ISO 9000:2008 Certification Practices on Operational Performance of Kenya Seed Company - Kipkorir Sitienei, Chris Simon; Sengwer, Abednego (JPAIR Multidisciplinary Research, 2016)
Kenya Seed Company has adopted organizational practices in line with ISO 9000:2008. The study analyzed the effect of ISO 9000:2008 certification practices of leadership, continual process improvement, people involvement, customer focus and mutual beneficial supplier relationship on operational performance of Kenya Seed Company, Kenya. The objective of the study was to determine the effect of these practices on operational performance. Anchored on stakeholder's management theory, the study used descriptive research design, stratified random sampling, a target population of 132 and a sample size of 99 respondents. Data were collected using a questionnaire whose validity and reliability were determined. It was analyzed using descriptive and inferential statistics and presented using frequency distribution tables. The ISO 9000:2008 practices had effects to a great extent and contributed to 65.6% of the variation in operational performance. The coefficients of y-intercept and these practices were significantly different from 0 because their p values were less than 0.05. The hypothesis "there is no significant relationship between ISO 9000:2008 certification practices and operational performance" was rejected. The mutual beneficial supplier relationship showed a negative gradient. There is the need for the company to assess the company's engagement with suppliers.
Keywords: Total quality management; ISO 9000; 2008 certification practices; operational performance; Kenya Seed; Company; descriptive research design; Kenya; Africa